Primary fiscal performance, economic growth, and public debt in Lebanon - Carole Ibrahim (Contemporary Economics, 2021)
Lebanese public debt has been accumulating since 1990, after the end of the civil war. Recently, concerns about the ability of the government to keep servicing its debt have emerged, particularly because the debt-to-GDP ratio reached almost 147% at the end of 2018. This study aims to examine whether a cointegrating relationship exists among primary fiscal performance, real economic growth, and public debt in Lebanon using an autoregressive distributed lag (ARDL) model between 2000 and 2018. The ARDL results suggest the non-existence of a cointegrating relationship and hence the unsustainability of the Lebanese public debt. The evidence of the short-run estimation indicates that better primary fiscal performance and a higher economic growth rate reduce Lebanese public debt in the short run. This study proposes that immediate reforms that increase the primary fiscal surplus and attract investors are crucial to prevent a debt crisis in the country.
Keywords: C22; H62; H63; 330; Primary fiscal performance; public debt; ARDL; economic growth; Lebanon